2015
DOI: 10.2147/ijwh.s68745
|View full text |Cite
|
Sign up to set email alerts
|

The utility of cardiac stress testing for detection of cardiovascular disease in breast cancer survivors: a systematic review

Abstract: BackgroundHeart function tests performed with myocardial stress, or “cardiac stress tests”, may be beneficial for detection of cardiovascular disease. Women who have been diagnosed with breast cancer are more likely to develop cardiovascular diseases than the general population, in part due to the direct toxic effects of cancer treatment on the cardiovascular system. The aim of this review was to determine the utility of cardiac stress tests for the detection of cardiovascular disease after cardiotoxic breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 56 publications
(106 reference statements)
2
17
0
1
Order By: Relevance
“…Our data suggest that myocardial hypoperfusion may be a very early event in this disease in which recurrent ischemia-reperfusion injury and microvascular dysfunction might play a crucial pathophysiological role in the development of perfusion defects. 8,9 Our results confirm, in a very early subset of SSc patients, previous CMR studies showing myocardial involvement in SSc patients. 8,24,25,[28][29][30][31] Taking together our data and the results already published by different groups, we may speculate that, in the early phase of the disease, cardiac perfusion defects may be recognized also in absence of fibrosis, whereas in long-standing disease, fibrosis may be the main alteration observed in the SSc heart.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our data suggest that myocardial hypoperfusion may be a very early event in this disease in which recurrent ischemia-reperfusion injury and microvascular dysfunction might play a crucial pathophysiological role in the development of perfusion defects. 8,9 Our results confirm, in a very early subset of SSc patients, previous CMR studies showing myocardial involvement in SSc patients. 8,24,25,[28][29][30][31] Taking together our data and the results already published by different groups, we may speculate that, in the early phase of the disease, cardiac perfusion defects may be recognized also in absence of fibrosis, whereas in long-standing disease, fibrosis may be the main alteration observed in the SSc heart.…”
Section: Discussionsupporting
confidence: 89%
“…Myocardial fibrosis was detected in 43% of patients unrelated to coronary artery distribution without sub‐endocardial layer involvement . Moreover, cardiac stress tests might be a helpful technique to highlight the occult microvascular involvement, which cannot be detected at rest …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential late effects of cancer treatment includes second malignancies, cardiovascular disease, obesity, osteoporosis, bone fractures, and other chronic conditions affecting physical and emotional well-being [2124]. The increased risk of cardiovascular disease among breast cancer survivors is due in part to the toxic effects of anticancer therapy (e.g., anthracyclines, trastuzumab, and radiation) on the cardiovascular system [25, 26]. …”
Section: Potential Long-term Side Effects Of Breast Cancer Treatmentmentioning
confidence: 99%
“…Cross-sectional studies of asymptomatic pediatric cancer survivors assessed with dobutamine stress echocardiography a number of years following anthracycline treatment (median 5.3-7 years) have shown cancer survivors have reduced posterior LV wall thickening, LVEF, and LV fractional shortening, decreased ratio of early to late peak mitral velocity (E/A), and increased LV wall stress during exercise compared to matched control subjects-demonstrating impairments in both systolic and diastolic reserve (148,149). Furthermore, the degree of impairment in cardiac reserve appears to relate to the dose of chemotherapy received (150). In contrast, Lanzarini et al found no differences in cardiac reserve in long-term (mean 7 years post-treatment) pediatric cancer survivors and matched sibling controls during low dose dobutamine stress echocardiography.…”
Section: The Utility Of Cardiac Reserve In Cancer Patients Exposed Tomentioning
confidence: 99%